1996
DOI: 10.1055/s-0038-1650551
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis and Lupus Anticoagulant

Abstract: Summary Background. A definite evidence in favour of an association of deep-vein thrombosis (DVT) with lupus anticoagulant (LA) in patients free from systemic lupus erythematosus is still lacking. Methods. In a case-control study, LA was determined in 176 consecutive outpatients who underwent phlebography because of the first episode of clinically suspected DVT of lower limbs. The association between DVT and LA was described using odds ratios (OR). Results. Contrast venography con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 4 publications
4
51
0
2
Order By: Relevance
“…[203][204][205] Indefinite anticoagulant therapy should be considered in patients with Ͼ1 episode of idiopathic proximal vein thrombosis, thrombosis complicating malignancy, or idiopathic venous thrombosis and homozygous factor V Leiden genotype, the antiphospholipid antibody syndrome, or deficiencies of antithrombin III, protein C, or protein S. 206 -208 Prospective cohort studies indicate that heterozygous factor V Leiden or the G20210A prothrombin gene mutation in patients with idiopathic venous thrombosis does not increase the risk of recurrence. 207,209 These recommendations are based on results of randomized trials 207 that demonstrated that oral anticoagulants effectively prevent recurrent venous thrombosis (risk reduction Ͼ90%), that treatment for 6 months is more effective than treatment for 6 weeks, 206 and that treatment for 2 years is more effective than treatment for 3 months. 208 …”
Section: Treatment Of Deep Venous Thrombosis or Pulmonary Embolismmentioning
confidence: 99%
“…[203][204][205] Indefinite anticoagulant therapy should be considered in patients with Ͼ1 episode of idiopathic proximal vein thrombosis, thrombosis complicating malignancy, or idiopathic venous thrombosis and homozygous factor V Leiden genotype, the antiphospholipid antibody syndrome, or deficiencies of antithrombin III, protein C, or protein S. 206 -208 Prospective cohort studies indicate that heterozygous factor V Leiden or the G20210A prothrombin gene mutation in patients with idiopathic venous thrombosis does not increase the risk of recurrence. 207,209 These recommendations are based on results of randomized trials 207 that demonstrated that oral anticoagulants effectively prevent recurrent venous thrombosis (risk reduction Ͼ90%), that treatment for 6 months is more effective than treatment for 6 weeks, 206 and that treatment for 2 years is more effective than treatment for 3 months. 208 …”
Section: Treatment Of Deep Venous Thrombosis or Pulmonary Embolismmentioning
confidence: 99%
“…Screening for mutations and conditions associated with thrombophilia (antithrombin, protein C, or protein S deficiency; factor V Leiden; prothrombin G20210A mutation; hyperhomocysteinemia; and lupus-like anticoagulants) was left to the discretion of treating physicians and was performed according to previously described methods. [29][30][31][32][33] Carriers of thrombophilia were classified as having spontaneous or secondary thrombosis according to their clinical presentation.…”
Section: Patientsmentioning
confidence: 99%
“…21 The enzyme-linked immunosorbent assay (ELISA) kit contains cardiolipin, anionic phospholipid, and ␤ 2 -glycoprotein I. Tests were considered positive if the values exceeded 15 phospholipid units (UPL)/mL and borderline when they were between 5 and 15 UPL/mL.…”
Section: Detection Of Apas and Other Routine Laboratory Determinationmentioning
confidence: 99%